2016
DOI: 10.5539/ies.v9n9p58
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Religious Attitude, Self-Efficacy, and Life Satisfaction in High school Teachers of Mahshahr City

Abstract: This study aims to investigate the relationship between the religious attitude, self-efficacy, and life satisfaction in high school teachers of Mahshahr City. To this end, 253 people of all high school teachers in Mahshahr City, in Iran were selected as the sample using the multistage cluster sampling method. For data collection, Glock and Stark's (1965) religious attitude questionnaires, Schwartz and Jerusalem's general self-efficacy questionnaire and Diener et al. 's (1985) life satisfaction questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…According to Bandura's theory of self-efficacy, the experience of childbirth delivery is one of the most important factors associated with women's self-efficacy [ 27 ]. According to studies, religious coping also affects self-efficacy [ 17 , 28 ] and may increase childbirth self-efficacy [ 29 ]. Callister cited childbirth as an opportunity to draw closer to God, as well as an opportunity to make religiosity more meaningful and the importance of supreme power in influencing birth and childbirth outcomes and a spiritual experience.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bandura's theory of self-efficacy, the experience of childbirth delivery is one of the most important factors associated with women's self-efficacy [ 27 ]. According to studies, religious coping also affects self-efficacy [ 17 , 28 ] and may increase childbirth self-efficacy [ 29 ]. Callister cited childbirth as an opportunity to draw closer to God, as well as an opportunity to make religiosity more meaningful and the importance of supreme power in influencing birth and childbirth outcomes and a spiritual experience.…”
Section: Introductionmentioning
confidence: 99%
“…It's the personality of an individual that determines the way they control their problems. According to Bigdeloo & Bozorgi (2016) in human life, their belief plays an important role and that is the basis that drives them to make different decisions in different situations. One of the main components of people's competence is referred to as self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of people's belief on self-efficacy have the ability to influence people's performance (weak, moderate, and strong) with similar skills in a different situation or even individual performance in various circumstances, hence Soleimani and Howeida (2013) have said that self-efficacy helps people to conduct extraordinary tasks using their skills. People's ability to process different stress factors can be caused by the difference in life satisfaction, thus, self -efficacy is believed as a reason that impact the life satisfaction that determines the extent to which people spend their time on conducting their task, resist against the problems, and show reflexivity in various situations (Bigdeloo & Bozorgi, 2016). Bagheri et al (2013) reported that self-efficacy is a critical factor that influences the success and failure in whole life (Bigdeloo & Bozorgi, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiritual is more popular with the human feelings, thoughts, and behaviours. Religious attitude also has a positive relationship with the belief and human's life satisfaction [16]. Zohar & Marshal argue that the spiritual has no connection with the religious doctrine or a certain belief.…”
Section: Introductionmentioning
confidence: 99%